The Sister-Brother Recognition Motif in the Albanian Folk Ballad: Meaning and Contexts within the National Culture - Dushi, Arbnora (Tautosakos darbai, 2020)
The motif of sibling relationships has been part of folklore since ancient times. In ancient civilizations, a marriage between brother and sister was considered the perfect pairing, as represented by the union of the moon and the sun, with its creative power on life on earth. According to written sources, Paganism supported this belief until the advent of Christianity, which sacrificed the sibling couple on the altar of monotheism, while it is also proven that the prohibition of incest originates from where nature transcends itself, where the social defeats the natural. This paper looks at this phenomenon among Albanians, and examines how it is treated in tradition, by analyzing the cultural background of the motif in folk ballads and in current artistic variations. How does the sister-brother relationship manifest in Albanian folk ballads? What is its origin? What do folk ballads say about the complexity of this relationship through time? I will draw on examples from Albanian folk ballads alongside anthropological theories built on family relationships, kinship, and cultural influences from a comparative perspective.